Case Study of Dispute Resolution in Delayed Payment of Debts Due to Force Majeure and Covid 2019 - Muhammad Ali (ISNU Nine-Star Multidisciplinary Journal, 2024)
The Covid-19 pandemic has caused various economic impacts, including delays in debt payments that have triggered legal disputes. This study aims to evaluate the resolution of disputes related to delays in debt payments due to Force Majeure conditions caused by the Covid-19 pandemic. Using normative legal research methods, this study analyzes relevant legal provisions, contracts, and court decisions related to Force Majeure cases in the context of the pandemic. This study also evaluates how positive law in Indonesia regulates and interprets Force Majeure in a pandemic situation. The results of the study indicate that the Covid-19 pandemic can be considered a Force Majeure condition in several cases, depending on the provisions of the contract and the judge's interpretation. Some courts grant a delay or exemption from payment obligations, while others reject the application if there is no Force Majeure provision in the contract or if the reasons submitted are considered ineligible. In conclusion, although Covid-19 can be recognized as Force Majeure, its effectiveness as a legal basis for delaying payments is highly dependent on the provisions of the contract and the judge's assessment. This study recommends writing a clearer Force Majeure clause in the contract to avoid future disputes.